'Hey, you there! Marketing!' On ideology and (mis)interpellation of the marketing educator as subject. Issue 3 (12th February 2022) - Gross, Nicole; Laamanen, Mikko
ABSTRACT: Mainstream marketing management is a disciplinary field essentially unruffled by ideological reflection. In this paper, we approach the subjectifying power of marketing ideology through Louis Althusser's work on interpellation, the process by which ideology calls its willing subjects into ideological belief and practice. Through our autoethnographic accounts, we develop a counterposition to the epistemic ideology of normative mainstream marketing management by accounting for misinterpellation to its ideology. Where interpellation outlines how a hegemonic marketing management ideology compels individuals to perform within the ideological apparatus as good educators and researcher subjects, the notion of misinterpellation opens avenues for conceiving resistance within the breaks in ideology to which all subjects are hailed.